Verivication of Considered Cause (Ta'lil al-Ahkam) in Worships from I'lam al-Muwaqi'in | تعليل الأحكام في العبادات من إعلام الموقعين - Zuhrotul Aini Mansur (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2015)
Verification of considered cause (ta’līl al-ahkām) together with the objectives of Shariah (maqāsid al-Sharī’ah) is among the most important issues discussed by the experts of Jurisprudence. This article analyses the procedures of establishing causes for a certain law according to Ibnu Qayyim Al-Jauziyah, a prominent salafi scholar who has written the subject in his book “I’lām al-muwāqi’īn” long time before Imam al-Syatibi who came up with theory of the objectives of Shariah. In his concept of ta’līl al-ahkām, Al-Jauziyah made a life interaction with texts of Islamic law resources through authentication of the texts, formulation of the causes and comparative studies on different opinions of scholars on ta’līl and tarjīh.